Efektivitas Pelatihan Konseling untuk Pencari Kerja dengan Model Kirkpatrick - Nindyati, Ayu Dwi; Sulistiobudi, Rezki Ashriyana; Syam, Gian Kautsar (Devotion : Jurnal Pengabdian Psikologi, 2023)
This counselling training activity aims to equip job introducers with counselling skills so they can do their role as counsellors for job seekers. The trainees are 180 introducers who are divided into 6 classes, so that each class has 30 participants. The implementation of the training is carried out for 2 days which is equivalent to 20 hours of training. The evaluation of the training program is carried out using level 2 evaluation based on Kirkpatrick evaluation method, which involves pre-training and post-training assessments. The results of this level 2 evaluation will explain whether this training is effective in terms of mastering the knowledge conveyed in the training. The evaluation results explained that 87% of participants increased their knowledge in counselling, 7% participants showed no difference in knowledge of counselling before and after the training program, 3% experienced a decrease in knowledge and 3% did not take the post-test. In order to improve the result of the training, it is recommended to reorganize the flow of the training program to ensure that the material covered is not too condensed within the two-day timeframe. It is suggested to extend the training duration to three days.